Reading Self-Efficacy in EFL Students' Critical Reading Strategies - Kusuma, Ivan Ilham (RETAIN, 2021)
Critical reading has become the key to students’ academic success. Many factors play an important role in the students’ critical reading, such as their reading self-efficacy. Considerable amount of research has found the contribution of reading self-efficacy towards students' reading strategy use. Reading self-efficacy can help students to determine the use of their knowledge and skill they have learned (Pajares, 2002), and explain why the same learner performs differently at different times. The present study thus attempted to find out the correlation between self-efficacy and EFL students' reading strategy use in Critical Reading. This study used quantitative method as the research design. Two questionnaires were distributed to 30 English Department students of a university in Indonesia. Positive moderate correlation was found between reading self-efficacy and reading strategy (r = 0.548, sig. at 0.01 level) so that this study supported that self-efficacy was correlated with the students’ reading strategy use.